Becoming a Police Officer: Self-Efficacy and Adversity Quotient in Facing Police Education - Gunawan Putra, Yousin; Handayani Harahap, Dewi; Rizqia, Gigih (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The National Police School (SPN PolDa DIY) is an educational institution that trains prospective members of the Indonesian National Police (Polri) tasked with maintaining public security and order. Education at SPN emphasizes not only academic aspects but also physical, mental, and technical skills to prepare non-commissioned officers (NCOs) who are ready for use in the field. SPN students face numerous educational demands, including physical readiness and high mental resilience. SPN Diktukba students face difficulties in enduring educational pressures. This condition is related to low adversity quotient (AQ), which is an individual's ability to respond to and survive life's difficulties (Stoltz, 2018). Students have problems with mental strength to survive and thrive despite being faced with challenges or difficulties in life (adversity quotient) and lack confidence in themselves to achieve their goals. Self-efficacy is one factor that influences adversity quotient. The hypothesis of this study is that there is a positive relationship between self-efficacy and adversity quotient in DikTukBa students. The subjects of this study were 95 DikTukBa students of SPN PolDa DIY. This study uses a quantitative approach with a questionnaire survey design that has been validated by professional judgment, with the results of Aiken's V for the self-efficacy variable being 0.75 while the adversity quotient variable was 0.833. The reliability of the self-efficacy variable was 0.983 and the adversity quotient variable was 0.982, meaning both variables were reliable. The results of this study showed a very significant positive relationship between self-efficacy and adversity quotient in Students of the Bintara Formation Education (Diktukba) of the Yogyakarta Special Region Police School (SPN Polda DIY) with the category of both variables being moderate with an effective contribution of 41.4%. From the results of the significance test, it shows that there is a probability value of 0.000 <0.05. Partially, self-efficacy has a very significant positive relationship with each dimension of the adversity quotient, namely the dimensions of control, origin & ownership, reach, and endurance. This finding strengthens the conclusion that self-confidence is the foundation that helps students have a higher fighting spirit.Sekolah Polisi Negara (SPN PolDa DIY) sebagai lembaga pendidikan pembentukan calon anggota Polri yang bertugas memelihara keamanan dan ketertiban masyarakat. Pendidikan di SPN tidak hanya menekankan aspek akademik, tetapi juga melatih fisik, mental, dan keterampilan teknis untuk menyiapkan bintara yang siap pakai di lapangan. Banyaknya tuntutan pendidikan yang harus dihadapi oleh para siswa SPN seperti kesiapan fisik dan ketahanan mental tinggi dari para siswanya. Siswa Diktukba SPN menghadapi kesulitan dalam bertahan menghadapi tekanan pendidikan. Kondisi ini berkaitan dengan rendahnya adversity quotient (AQ), yaitu kemampuan individu dalam merespon dan bertahan terhadap kesulitan hidup (Stoltz, 2018). Siswa memiliki masalah pada kekuatan mental untuk bertahan dan berkembang meskipun dihadapkan pada tantangan atau kesulitan hidup (adversity quotient) dan tidak yakin pada diri sendiri untuk bisa mencapai tujuan. Self-efficacy menjadi salah satu faktor yang mempengaruhi adversity quotient. Hipotesis penelitian ini terdapat hubungan positif antara self-efficacy dan adversity quotient pada Siswa DikTukBa. Subjek penelitian ini adalah 95 siswa DikTukBa SPN PolDa DIY. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei kuesioner yang telah diuji validasi oleh profesional judgement, dengan hasil Aiken’s V variabel self-efficacy adalah 0.75 sedangkan variabel adversity quotient adalah 0.833. Reliabilitas varibel self-efficacy 0,983 dan variabel adversity quotient 0,982 artinya kedua variabel reliabel. Hasil dari penelitian ini terdapat hubungan positif sangat signifikan antara self-efficacy dan adversity quotient pada Siswa Pendidikan Pembentukan Bintara (Diktukba) Sekolah Polisi Negara Kepolisian Daerah Daerah Istimewa Yogyakarta (SPN Polda DIY) dengan kategori kedua variabel sedang dengan sumbangan efektif 41,4%. Dari hasil pengujian signifikansi menunjukkan bahwa terdapat nilai probabilitas sebesar sebesar 0,000 < 0,05. Secara parsial self-efficacy memiliki hubungan positif yang sangat signifikan dengan setiap dimensi dari adversity quotient, yaitu dimensi control, origin & ownership, reach, dan endurance.Temuan ini memperkuat kesimpulan bahwa keyakinan diri adalah fondasi yang membantu siswa memiliki daya juang yang lebih tinggi.